Carnivores and Communities: A Case Study of Human-Carnivore Conflict Mitigation in Southwestern Alberta - Morehouse, Andrea T.; Hughes, Courtney; Manners, Nora; Bectell, Jeff; Bruder, Tony (Frontiers in Ecology and Evolution, 2020)
Facilitating long-term coexistence between people and large carnivores is a persistent, global conservation challenge. Evidence-based decisions to help design and implement programs that promote coexistence between people and carnivores are required. Using a case study approach, we evaluated the effectiveness of conflict mitigation efforts of a community-based program in southwestern Alberta, Canada: the Waterton Biosphere Reserve’s (WBR) Carnivores and Communities Program (CACP). The CACP’s overall goal is to support coexistence of people and large carnivores through initiatives including reducing livestock loss, damage to stored crops, and safety risks from carnivores by engaging residents in hands-on programming. We used an online survey to assess program participants’ general awareness of and motivation to engage in the CACP, safety risks associated with living with large carnivores, and attractant management and deadstock removal programming. We received 116 completed surveys. Survey results indicated that participants felt the CACP effectively reduced conflicts with large carnivores, increased their sense of safety when living with large carnivores, and enabled them to learn skills and gain confidence in using mitigation tools (e.g., bear spray). We also evaluated temporal trends in large carnivore conflicts using occurrence records (i.e., complaint data) from 1999 through 2016. We classified these data into incidents (e.g., situations where carnivores caused property damage, obtained anthropogenic food, killed or attempted to kill livestock or pets) and focussed on incidents related to attractants, including deadstock. We focus our incident review on grizzly bears because most agricultural attractant incidents in the study area are caused by grizzly bears. We used a Chow test to evaluate if the 2009 CACP commencement represented a break point or structural change in the data. Although total reported incidents increased from 1999 through 2016, we show both reported attractant and deadstock-based incidents changed from increasing to decreasing after the CACP implementation in 2009. Our results demonstrate the effectiveness of a contextually specific, community-based approach to addressing human-carnivore conflicts. More broadly, our evaluation and lessons learned provide other conservation organizations with a useful framework for addressing human-carnivore or other wildlife conflicts.